The effect of exercise intervention on improving sleep in menopausal women: a systematic review and meta-analysis - Qian, Jialu; Sun, Shiwen; Wang, Man; Sun, Yaping; Sun, Xiangyu; Jevitt, Cecilia; Yu, Xiaoyan (Frontiers in Medicine, 2023)
Background Sleep disturbance is common in menopausal women and negatively affects their quality of life and could cause increased risks of other menopause-related diseases. Objective This systematic review aims to synthesize evidence regarding the effects of exercise interventions on improving sleep in menopausal women. Methods A comprehensive search in seven electronic databases for randomized controlled trials (RCTs) was performed on June 3, 2022. The systematic review included seventeen trials, ten of which provided data for the meta-analysis. The effects on outcomes were presented as mean differences (MDs) or standard mean differences (SMDs) and their 95% confidence intervals (CI). Cochrane risk-of-bias tool was used in quality assessment. Results The results suggest that exercise intervention significantly reduces insomnia severity (SMD = −0.91, 95% CI = −1.45 to −0.36, Z = 3.27, P = 0.001) and alleviates sleep problems (MD = −0.09, 95% CI = −0.17 to −0.01, Z = 2.20, P = 0.03). For sleep quality, the results showed that insignificant differences were found between the exercise intervention and the control groups (MD = −0.93, 95% CI = −2.73 to 0.87, Z = 1.01, P = 0.31). The results of the subgroup analysis indicated that more apparent effects of exercise intervention were found among women with sleep disorders than among women without sleep disorders. Which exercise intervention duration was more beneficial to sleep outcomes could not be judged. Overall, there was a moderate risk of bias in the primary studies. Conclusion According to this meta-analysis, exercise interventions can be recommended for menopausal women to improve their sleep. High-quality RCTs applying different types of exercise (e.g., walking, yoga, meditative exercise and so on) with different intervention durations as well as subjective and objective sleep assessment are warranted. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022342277, identifier: CRD42022342277.